The Condition of MSMEs during the COVID-19 Pandemic: Case Study of MSMEs at Mba Yuni Food Stalls - Giri Pamungkas; Fitri Komariyah (INCOME: Innovation of Economics and Management, 2022)
Micro, Small and Medium Enterprises (MSMEs) have a crucial role in increasing the country's gross domestic product. however, since COVID-19 hit globally at the end of 2019, and there have been many government policies in force in tackling the COVID-19 pandemic, many business actors have experienced a drastic decline in income and not a few have been unable to maintain their businesses which led to the closure, one of which was the Mba Yuni Food Stall business. This study aims to get an illustration of the condition of MSMEs in the culinary and beverage sector during the COVID-19 pandemic at a food stall. This study was conducted for 3 months from March to June 2022. The research method used is descriptive quantitative using purposive sampling techniques using information sources in the form of field information interviews using samples of MSMEs at Mba Yuni Food Stalls. The results showed that the profit obtained by msMEs of Warung Makan Mba Yuni in the city of Surabaya during the COVID-19 pandemic had a relatively compound figure. This data shows that MSMEs at Mba Yuni Food Stalls are still unable to maximize their business potential, one of which is caused by COVID-19 and the policies implemented by the government during the COVID-19 pandemic. The Large-Scale Social Restrictions policy implemented by the government requires business owners to cut business active time only until 21.00 WIB and reduce the number of consumers by 50% for dine-in. The government's policy of limiting working hours during the COVID-19 pandemic is an important factor in the decline in the business income of MSMEs at Warung Makan Mba Yuni during the COVID-19 pandemic.